Evolution of parthenogenetic reproduction in Caucasian rock lizards: A review. Issue 2 (14th May 2022) - Arakelyan, Marine; Spangenberg, Victor; Petrosyan, Varos; Ryskov, Alexey; Kolomiets, Oksana; Galoyan, Eduard
Abstract: Despite numerous works devoted to hybrid origin of parthenogenesis in reptiles, the causes of hybridization between different species, resulting in the origin of parthenogenetic forms, remain uncertain. Recent studies demonstrate that sexual species considered parental to parthenogenetic rock lizards ( Darevskia spp.) avoid interspecific mating in the secondary overlap areas. A specific combination of environmental factors during last glaciation period was critical for ectotherms, which led to a change in their distribution and sex ratio. Biased population structure (e.g., male bias) and limited available distributional range favored the deviation of reproductive behavior when species switched to interspecific mates. To date, at least 7 diploid parthenogenetic species of rock lizards ( Darevskia, Lacertidae) originated through interspecific hybridization in the past. The cytogenetic specifics of meiosis, in particular the weak checkpoints of prophase I, may have allowed the formation of hybrid karyotypes in rock lizards. Hybridization and polyploidization are 2 important evolutionary forces in the genus Darevskia . At present, throughout backcrossing between parthenogenetic and parental species, the triploid and tetraploid hybrid individuals appear annually, but no triploid species found among Darevskia spp. on current stage of evolution. The speciation by hybridization with the long-term stage of diploid parthenogenetic species, non-distorted meiosis, together with the high ecological plasticity of Caucasian rock lizards provide us with a new model for considering the pathways and persistence of the evolution of parthenogenesis in vertebrates.